Quality of life of glaucoma patients under medical therapy with different prostaglandins - Paletta Guedes RA (Dove Medical Press, 2012)
Ricardo Augusto Paletta Guedes,1–3 Vanessa Maria Paletta Guedes,1–3, Sirley Maria Freitas,2 Alfredo Chaoubah11Federal University of Juiz de Fora, Juiz de Fora, Minas Gerais, Brazil; 2Paletta Guedes Ophthalmological Center, Juiz de Fora, MG, Brazil; 3Santa Casa de Misericórdia Hospital, Juiz de Fora, Minas Gerais, BrazilPurpose: To assess the quality of life of glaucoma patients under medical therapy with different prostaglandin analogs.Methods: A cross-sectional study of consecutive glaucoma patients was designed. We assessed the patients' quality of life through the Brazilian 25-question version of the National Eye Institute Visual Functioning Questionnaire, comprising 12 subscales (general health, general vision, ocular pain, near vision, distance vision, social function, mental health, role limitations, dependency, driving, color vision, and peripheral vision) and a total composite score. Clinical features, including current medical treatment, were obtained from each patient's medical record. Three groups of patients were identified according to the prostaglandin in use: bimatoprost, latanoprost, or travoprost. The main outcome measures were: mean score in each subscale and mean total composite score.Results: The mean total composite score for the whole group was 70.60. The bimatoprost, latanoprost, and travoprost groups had the following mean composite scores, respectively: 56.56, 77.36, and 71.08 (P = 0.001, analysis of variance [ANOVA]). Latanoprost and travoprost results were similar, and both were superior to bimatoprost. Most subscales had similar results. The subscale with the lowest score for all groups was general health. Groups were homogenous and comparable.Conclusion: There is a difference in the quality of life between glaucoma patients using prostaglandin analogs. It seems that bimatoprost users have lower QoL when compared to latanoprost and travoprost users.Keywords: glaucoma, medical treatment, prostaglandin analogs, quality of life